2013
DOI: 10.1088/0957-4484/24/38/384006
|View full text |Cite
|
Sign up to set email alerts
|

Volatile and nonvolatile selective switching of a photo-assisted initialized atomic switch

Abstract: A photo-assisted atomic switch, which has a photoconductive molecular layer in a gap of about 20 nm between an Ag2S electrode and a Pt electrode, is set to a conventional gap-type atomic switch operation mode by light irradiation with the application of a small bias that precipitates Ag atoms from an Ag2S electrode. After this initialization, the switch operates only with application of a bias. In this study, we also found that after the set-operation a photo-assisted initialized atomic switch shows different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…The mechanism of operation of these devices is known as the formation and rupture of a conductive bridge path (e.g., metallic filament) in solid-electrolyte layers. [36][37][38][39] Because extrinsic Ag ions have a large diffusion coefficient (i.e., are fast diffusers), Ag ions can easily migrate in the ZnO matrix along the applied electric field. 40,41 After they reached the bottom electrode through the ZnO layer without agglomerating, they formed filaments by combining with electrons at the bottom electrode interface (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of operation of these devices is known as the formation and rupture of a conductive bridge path (e.g., metallic filament) in solid-electrolyte layers. [36][37][38][39] Because extrinsic Ag ions have a large diffusion coefficient (i.e., are fast diffusers), Ag ions can easily migrate in the ZnO matrix along the applied electric field. 40,41 After they reached the bottom electrode through the ZnO layer without agglomerating, they formed filaments by combining with electrons at the bottom electrode interface (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the electric-field has an important effect on filament instability. 38,43,44 In this work, a weak electric field was applied to the electrode. It could not reach the top electrode because low voltage was applied to the 40-nm-thick oxide layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cu cations are reduced at the Pt electrode/TiO 2 electrolyte interface, where Cu clusters are formed through nucleation followed by a growth process (Figure 5a,b). Hino et al presented a light irradiation assisted atomic switch, [46] and Liu et al suggested the presence of δ-Cu phase incurred volatile switching. There are several previous studies dealing with threshold switching behavior of ECM-based ReRAM.…”
Section: Resultsmentioning
confidence: 99%
“…18 This limitation is for instance utilized in volatile and nonvolatile selective switching of photo-assisted atomic switches. 19,20 Decision making based on these atomic switches was very recently proposed theoretically by Kim et al 21 In this study, we extend the function of atomic switches so that they can achieve the 'tug of war' operation. In conventional gap-type atomic switches, growth and shrinkage of a metal filament between two electrodes, a solid electrolyte electrode such as α-Ag 2+δ S and a counter metal electrode, are controlled, see Fig.…”
Section: Introductionmentioning
confidence: 95%